Determinación de la época adecuada para la aplicación del herbicida accent (nicosulfuron) con interacción de niveles de fertilización edáfica, en el cultivo de maíz (Zea mays L.) en la zona de Babahoyo provincia de Los Ríos - Cabero Acosta, Byron Armando (2016)
SUMARY The investigation was made in the lands of the Farm "San Pablo of the UTB, located in the Km 7,5 of the road Babahoyo-Montalvo. The objective of the work was to determine the most appropriate time for the application of the herbicide ACCENT (nicosulfuron), interaccionando levels of fertilization edáfica in corn, to evaluate its effect on the grain yield and development of the cultivation. 24 treatments settled down with three repetitions and they were distributed in a you parcel divided with factorial arrangement. The treatments were formed by the herbicides, fertilizers and application times. For the evaluation of stockings the test was used from Tukey to 5 % significance. At the end of the cycle of the cultivation plant height, height of ear insert, ear diameter was evaluated, ear longitude, days to flowering, days to crop, weight 100 grains, yield for hectare, control percentage, toxicity index and economic analysis. The results determined that the application of ACCENT in dose of 40 gr/Ha, control the overgrowths in the cultivation of corn with ranges of the 67 to 78%. Likewise to apply ACCENT in dose of 40 gr/Ha, it doesn't cause fitotoxicidad in the hybrid ones evaluated (DK-7088 and Triunfo), being the values among 2 and 3,5 of the scale of the ALAM, being considered little damage. The Hybrid of corn DK-7088, applying ACCENT in dose of 40 g/ha to the 12 days after sowing, fertilizing with 289-45-198 kg/ha N-P-K showed the biggest yield with 10,53 Tm/ha.